Analisis Penerjemahan Tema Topikal pada Buku Cerita Anak Bilingual ‘Sangkuriang’ - Zulia Karini (Institut Agama Islam Negeri Purwokerto, 2016)
Abstract In the practice of translation, we often do not pay attention to the way the information is distributed in the text. The information which is being focused is old information that has been mutually known by the writer and the reader and it is usually placed at the front, called Theme, while other information is new information that is only known by the authors and it is usually placed later, called Rheme. Topical theme is the theme related to how the subject matter discussed in the clause or sentence. Topical themes are divided into two types, namely Marked Topical Theme, Unmarked Topical Theme. The analysis of Topical Theme was conducted to determine whether there was a shift in the meaning of the translation of the source language text into the target language text.